Menschenrechte und christliche Ethik: eine systematische Verhältnisbestimmung - Witschen, Dieter (Zeitschrift für katholische Theologie, 1998)
Since human rights have a morally based position, christian ethics can make a contribution to the justifying and realisation of human rights. This contribution can be summarized under four headings: 1. In relation to the bearers of these rights, a christian ethic affirms the universality of human rights. 2. Those to whom the demands for human rights are directed are in the first place states, but in a further necessary context also non-state organizations, of which the Church is one. 3. With regard to their contents, there are convergencies between human rights, by which the basic values, which make the development of a human being possible, are protected, and a christian ethic. 4. The latter discipline interprets the human rights, as far as its character of a natural law is concerned, and facilitates their overall integration in a metaethical context.